Diets rich in saturated and polyunsaturated fatty acids: Metabolic shifting and cardiac health - Diniz, Y. S.; Cicogna, A. C.; Padovani, C. R.; Santana, L. S.; Faine, L. A.; Novelli, ELB (Elsevier B.V., 2004)
OBJECTIVE: the aim of this study was to determine the effects of diets rich in saturated and polyunsaturated fatty acids on metabolic pathways and the relation of metabolic shifting to oxidative stress in cardiac tissue.METHODS: Male Wistar rats (age, 60 d; n = 10) were fed with a control low-fat diet, a diet rich in saturated fatty acids (SFAs), or a diet rich in polyunsaturated fatty acids (PUFAs). After 5 wk of treatment, sera were used for protein and lipid determinations. Protein, glycogen, triacylglycerol, lactate dehydrogenase, citrate synthase, beta-hydroxyacyl coenzyme-A dehydrogenase, catalase, glutathione peroxidase, superoxide dismutase, lipoperoxide, and lipid hydroperoxide were measured in cardiac tissue.RESULTS: the SFA group had higher triacylglycerol, cholesterol, low-density lipoprotein cholesterol, and atherogenic index (ratio of cholesterol to high-density lipoprotein) than did the PUFA and control groups. The PUFA group had low serum cholesterol, triacylglycerol, and low-density lipoprotein cholesterol as compared with the SFA group. SFA increased myocardial lipid hydroperoxide and diminished glutathione peroxidase. Despite the beneficial effects on serum lipids, the PUFA diet led to the highest levels of myocardial lipoperoxide and lipid hydroperoxide and diminished superoxide dismutase and catalase activities. The PUFA effects were related to increased feed efficiency, increased susceptibility to lipoperoxidation, and metabolic shifting in cardiac tissue. PUFA elevated triacylglycerol levels and decreased myocardial glycogen concentrations. The ratios of lactate dehydrogenase to citrate synthase and beta-hydroxyacyl coenzyme-A dehydrogenase to citrate synthase were increased, indicating myocardial reduction of tricarboxylic acid cycle.CONCLUSIONS: PUFAs have been recommended as a therapeutic measure in preventive medicine to lower serum cholesterol, but PUFAs increased oxidative stress in the heart by providing cardiac susceptibility to lipoperoxidation and shifting the metabolic pathway for energy production. The control diet, which was much lower in calories and fat, produced better overall clinical outcomes, better fat profiles, and less oxidative stress than did the diets rich in fatty acids.
Keywords: polyunsaturated fatty acid; saturated fatty acid; diets; heart; oxidative stress; lipids; serum